1996
DOI: 10.1002/hep.510240334
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Prostaglandin Synthesis in Cultured Liver Cells by Ccl4

Abstract: (PGD 2 ) and smaller amounts of prostaglanThe contribution of hepatocytes to liver prostaglandin din E 2 (PGE 2 ), prostaglandin F 2a (PGF 2a ), and other arachisynthesis is controversial, partly because hepatocytes of donic acid metabolites. 5 However, there is no consensus varying purity have been studied. In this study, prostawhether hepatocytes have an active cyclooxygenase pathglandin synthesis was examined in conventional and riway. 1 We previously studied this question using homogenates cin-purified r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
18
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Moreover, negligible amounts of F 2 -isoprostanes are released by cultured Kupffer cells when challenged with CCl 4 . 43 Also, it has been shown 18,19 that both free and total (sum of free plus esterified) isoprostanes are dramatically increased in the liver after CCl 4 intoxication.…”
mentioning
confidence: 99%
“…Moreover, negligible amounts of F 2 -isoprostanes are released by cultured Kupffer cells when challenged with CCl 4 . 43 Also, it has been shown 18,19 that both free and total (sum of free plus esterified) isoprostanes are dramatically increased in the liver after CCl 4 intoxication.…”
mentioning
confidence: 99%
“…We previously investigated the toxicity of C C 4 toward isolated rat hepatocytes, using a new hepatocyte purification method which permits total elimination of Kupffer and endothelial cells (Johnston & Kroening 1996;Johnston & Jasuja 1994). These experiments showed that a CC14 partial pressure of 35 mmHg caused no increase in hepato-son, Lincoln Park, NJ, USA) and changed to a serum-free hormonally-defined medium as previously described (Johnston & Jasuja 1994).…”
mentioning
confidence: 99%
“…Typically, hepatocytes were used after 48 hr in serum-free medium. Where indicated, hepatocytes were purified on the first day of culture using ricin A chain to selectively destroy Kupffer and endothelial cells (Johnston & Jasuja 1994;Johnston & Kroening 1996). Control experiments previously showed no effect of ricin selection on protein synthesis or other hepatocyte-specific functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocyte monolayer cultures were incubated with varying concentrations of CCl 4 gas as described previously. 24 Experiments were performed using 0 to 2 mL liquid CCl 4 , corresponding to 0.591 L gas volume at the local atmospheric pressure (1,600 m), in a chamber with a 5-L volume. At the end of the incubation period, the activities of cytosolic ␤-glucosidase, ALT, and LDH were determined in the culture medium and in the cells after homogenization in lysis buffer as described above.…”
mentioning
confidence: 99%